Proposal of orienting basis of the action to stimulate the conforming abilities of personal development from the subject “Psychology of personality” in Municipal Universitarian Schools conditions - Diaz pupo, Arledys (Pensando Psicología, 2010)
The article presents the results of the research “Learning to learn in Psychology students: a proposal of historical-culturalist intervention”, conducted by the group Scientific studies about human development, of the Psychology Faculty of Universidad de Holguín, Cuba. The investigation starts from historical-cultural references and from a complex perspective as epistemological basis. Its antecedents are teaching and investigative experiences and the experimental systematizations. Theoretical and empirical methods were used; in the latter, the formative experiment was the fundamental axis. Among the most important results stands out the general founding of the theoreticalmethodological elements that the orienting basis of the action (oba) must have to promote the development of the strategic abilities of learning, as well as the description of the structure and function of each of the OBA’s systems, and the implications that the implementation of the historical-cultural requirements has over educational innovation or educational practice.